2021
DOI: 10.21037/apm-21-907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of upper gastrointestinal bleeding on prognosis of middle-aged patients with acute ischemic stroke: a retrospective study

Abstract: Background: Upper gastrointestinal bleeding (UGIB) is a common complication of acute ischemic stroke (AIS), but the effect of UGIB on the prognosis of middle-aged AIS patients is not clear.Methods: Patients with AIS admitted to our hospital from January 2011 to December 2015 were eligible to be included in this study. All included patients were divided into UGIB and non-UGIB groups. Some clinical characteristics were retrospectively collected. Primary outcomes were all-cause mortality within 1, 3, and 5 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…Previous studies have indicated that the occurrence of UGIB was correlated with a higher 5-year mortality rate, 26 which is in contrast to our findings. The reason for this discrepancy may be that the UGIB rate in the cohort of patients we considered was too low, we also focused on in-hospital mortality rather than 5-year mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have indicated that the occurrence of UGIB was correlated with a higher 5-year mortality rate, 26 which is in contrast to our findings. The reason for this discrepancy may be that the UGIB rate in the cohort of patients we considered was too low, we also focused on in-hospital mortality rather than 5-year mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…We noticed that, from the results of subgroup analysis, most of the groups that did not reveal the association of PPI prophylaxis with poor outcome after one year were the ones that included patients who had a high risk of GIB. For example, it is commonly recognized that patients receiving antithrombotic agents experience an increased risk of GIB [ 29 , 30 ]. Blood glucose in patients with GIB was 0.8 mmol/L higher than that in patients without GIB.…”
Section: Discussionmentioning
confidence: 99%